Periodontal and Peri-Implant Health Status in Traditional vs. Heat-Not-Burn Tobacco and Electronic Cigarettes Smokers: A Systematic Review - Francesco D'Ambrosio; Massimo Pisano; Alessandra Amato; Alfredo Iandolo; Mario Caggiano; Stefano Martina (MDPI AG, 2022)
The aim of the present systematic review was to evaluate and possibly differentiate the effects of traditional cigarettes, heat-not-burn tobacco, and electronic cigarettes on periodontal and peri-implant health status. Electronic cigarettes and heat-not-burn tobacco have become very popular in recent years and have been proposed to consumers as a safer alternative to conventional tobacco smoke, although their effect on periodontal and peri-implant health remains unclear. The study protocol was developed according to PRISMA guidelines, and the focus question was formulated according to the PICO strategy. A literature search was conducted across PubMed/MEDLINE and the COCHRANE library from 2003 to April 2022. From the 1935 titles initially identified, 18 articles were finally included in the study and extracted data were qualitatively synthesized. It may be carefully concluded that e-cigarettes may cause attenuated clinical inflammatory signs of periodontitis and, hypothetically, of peri-implantitis when compared to conventional tobacco smoke. Both alternative smoking products, containing nicotine, may likewise exert negative effects on periodontal and peri-implant health, as demonstrated by in vitro studies. Further investigations are needed to assess the impact of electronic cigarettes and heat-not-burn tobacco products on periodontal and peri-implant health status.